Employee-Employer Perception towards Healthcare Scheme for Employees of Business Enterprises in Bangladesh: An Empirical Study - Uddin, Mohammed Asraf; Alam, Mohammad Mofidul; Hossain, Shahadat (IIUC Studies, 2009)
There is an increasing need for the management of the large and medium scale businesses to provide health care schemes for their employees as people in all areas as well as commercial area are becoming more health conscious. This study firstly aims at understanding the present status of health care facilities available at the workplace from the viewpoint of both employees and employers. The study then asked the respondents whether a health care scheme is feasible in their organizations and how could they benefit from the health care scheme. Some actions have been suggested in terms of the overall findings that were revealed in the study. Finally the prospect of such health care scheme has been evaluated to understand how far would employers go in keeping their workers happy for ensuring health care for this vulnerable sector. Doi: IIUC Studies Vol.2 2004